Analisis Du Pont dalam menilai kinerja keuangan pada perum perumnas proyek Kepulauan Riau - Ante, Jeine Margareta; Budiarso, Novi Swandari; Gerungai, Natalia Y. T. (Manajemen Bisnis dan Keuangan Korporat, 2025)
This study applies the Du Pont analysis method to evaluate the financial performance of Perum Perumnas Riau Islands Project for the period 2020–2024. The Du Pont framework decomposes Return on Equity (ROE) into three components: net profit margin, asset turnover, and equity multiplier, allowing a comprehensive assessment of profitability, efficiency, and leverage. This research employs a quantitative approach using secondary data from the company’s financial statements. The findings reveal that the company’s financial performance improved significantly over the study period, with ROE consistently increasing and exceeding the industry average. The improvement was mainly driven by higher asset utilization efficiency and stronger returns on equity. However, the analysis also indicates a growing dependence on debt, which increases financial risk. These results highlight the importance of effective risk management strategies to ensure sustainable growth and maintain long-term financial stability.